OWL2 benchmarking for the evaluation of knowledge based systems. - Sher Afgun Khan; Muhammad Abdul Qadir; Muhammad Azeem Abbas; Muhammad Tanvir Afzal; Muhammad Tanvir Afzal (PLoS ONE)
OWL2 semantics are becoming increasingly popular for the real domain applications like Gene engineering and health MIS. The present work identifies the research gap that negligible attention has been paid to the performance evaluation of Knowledge Base Systems (KBS) using OWL2 semantics. To fulfil this identified research gap, an OWL2 benchmark for the evaluation of KBS is proposed. The proposed benchmark addresses the foundational blocks of an ontology benchmark i.e. data schema, workload and performance metrics. The proposed benchmark is tested on memory based, file based, relational database and graph based KBS for performance and scalability measures. The results show that the proposed benchmark is able to evaluate the behaviour of different state of the art KBS on OWL2 semantics. On the basis of the results, the end users (i.e. domain expert) would be able to select a suitable KBS appropriate for his domain.